2022
DOI: 10.1007/s12274-022-5043-6
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of graphene oxide-supported multilayer-quantum dots nanofilm into multiplex lateral flow immunoassay: A rapid and ultrasensitive point-of-care testing technique for multiple respiratory viruses

Abstract: A lateral flow immunoassay (LFA) biosensor that allows the sensitive and accurate identification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other common respiratory viruses remains highly desired in the face of the coronavirus disease 2019 pandemic. Here, we propose a multiplex LFA method for the on-site, rapid, and highly sensitive screening of multiple respiratory viruses, using a multilayered film-like fluorescent tag as the performance enhancement and signal amplification tool. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Such data set outcomes indicated that Ti 3 C 2 -QD-ICA had a high sensitivity and good colorimetric performance for concomitantly detecting H1N1 and SARS-CoV-2 real viruses. The method was compared with other recently reported biosensors in terms of sensitivity, reproducibility, specificity, and assay time in Table S1. ,, Our method demonstrated a relatively superior assay performance among these assays. The Ti 3 C 2 -QD-ICA has the potential to be a valuable POCT instrument focusing upon accurate and rapid clinical determination of respiratory viruses because of its good stability, multiplex detection capability, easy operation, cheap cost, and short detection time.…”
Section: Resultsmentioning
confidence: 99%
“…Such data set outcomes indicated that Ti 3 C 2 -QD-ICA had a high sensitivity and good colorimetric performance for concomitantly detecting H1N1 and SARS-CoV-2 real viruses. The method was compared with other recently reported biosensors in terms of sensitivity, reproducibility, specificity, and assay time in Table S1. ,, Our method demonstrated a relatively superior assay performance among these assays. The Ti 3 C 2 -QD-ICA has the potential to be a valuable POCT instrument focusing upon accurate and rapid clinical determination of respiratory viruses because of its good stability, multiplex detection capability, easy operation, cheap cost, and short detection time.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, two-dimensional nanomaterials, such as graphene oxide (GO), titanium carbide, black phosphorus, and molybdenum disulde, have been used as excellent carriers for the construction of ultrasensitive biosensors due to their massive surface areas, exibility, superior stability, and abundant surface groups. [31][32][33] Our previous works also demonstrated the combination of monolayer GO and other nanoparticles (e.g., QDs, AuNPs, and AgNPs) as high-performance lm-like nanotags for LFIA methods. [34][35][36] For example, the GO nanosheet loaded one layer of dense QDs can act as exible uorescent tags for simultaneous detection of two kinds respiratory pathogens in real respiratory tract samples via LFIA strip.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its distinct characteristics, including low cost, good robustness, simplicity, and convenience, the immunochromatographic assay (ICA) has been regarded as the most popular and mature rapid detection technology and is widely used in infectious disease diagnosis and identification of various pathogens. Traditional ICA methods, which are based on colloidal AuNPs to output visual colorimetric signals, have two shortcomings, namely, lack of sensitivity and poor quantitative capacity to be solved. To improve the performance of ICA, researchers have recently introduced novel signal tags, such as fluorescent microspheres, quantum dots (QDs), magnetic particles, surface-enhanced Raman scattering (SERS) tags, and nanoenzyme tags to replace traditional AuNPs and provide more sensitive and readable signals (fluorescence, magnetic, SERS, and chemiluminescence) for quantitative detection. However, these novel ICA biosensors usually need large or precision instruments and lack visual detecting performance, which weakens the on-site detection ability of immunochromatography.…”
Section: Introductionmentioning
confidence: 99%